1999
DOI: 10.3147/jsfp.34.139
|View full text |Cite
|
Sign up to set email alerts
|

Vibriostatic Bacteria Isolated from Rearing Seawater of Oyster Brood Stock: Potentiality as Biocontrol Agents for Vibriosis in Oyster Larvae.

Abstract: ABSTRACT--To apply the biocontrol technique for vibriosis of larvae of the Pacific oyster, Crassostrea gigas, we isolated marine bacterial strains from the rearing seawater of oyster brood stock and screened the strains having suppressive activity for the growth of pathogenic vibrios. Twelve strains of the 51 isolated strains clearly showed inhibitory effects on growth of three vibrios (Vibrio alginolyticus, V. tubiashii and Vibrio sp.) by a smear method with agar plates. One strain (S21) demonstrated the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…It is possible that some of these strains could be used as probiotics. Strains that possess antagonistic effects on pathogenic Vibrio species have been isolated from scallop (Pecten maximus) larvae (Ruize-Ponte et al 1999), and similar findings have been reported from Chilean scallops (Argopecten purpuratus) (Riquelme et al 1996b(Riquelme et al , 1997Jorquera et al 1999) and from studies with Pacific oyster (Crassostrea gigas) larvae (Douillet and Langdon 1993;Gibson et al 1998;Nakamura et al 1999), suggesting that beneficial strains may be relatively common in bivalve larval cultures and that their potential should be further investigated.…”
Section: Discussionmentioning
confidence: 59%
“…It is possible that some of these strains could be used as probiotics. Strains that possess antagonistic effects on pathogenic Vibrio species have been isolated from scallop (Pecten maximus) larvae (Ruize-Ponte et al 1999), and similar findings have been reported from Chilean scallops (Argopecten purpuratus) (Riquelme et al 1996b(Riquelme et al , 1997Jorquera et al 1999) and from studies with Pacific oyster (Crassostrea gigas) larvae (Douillet and Langdon 1993;Gibson et al 1998;Nakamura et al 1999), suggesting that beneficial strains may be relatively common in bivalve larval cultures and that their potential should be further investigated.…”
Section: Discussionmentioning
confidence: 59%
“…The strain was selected for its in vitro inhibitory properties against the fish pathogens Aeromonas hydrophila, Pseudomonas fluorescens and Edwardsiella tarda using the double-layer (Dopazo et al 1988), cross-streak (Mayr-Harting et al 1972) and parallel-streak (Nakamura et al 1999) techniques. The above fish pathogenic strains were isolated from ulcers on the skin and fins of diseased Carassius auratus (Linnaeus) at the Central Institute of Fisheries Education, Mumbai, India, and their identities were confirmed following the procedures of Krieg and Holt (1984).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…The first mortality observed within 2 h post-injection. All 10 fish died where β-haemolytic Aeromonas hydrophila N 10 P were inoculated @ 6.37x10 10 cells/fish in 24 h of post-injection; whereas 9 out of 10 challenged fish died in the stock inoculated with 6.37x10 9 cells/fish within 24 h. All the fish in third stock containing 10 fish, which were inoculated with 6.37x10 8 cells/fish died within 48 h post-injection and 6.37x10 7 cells/fish inoculated stock recorded two mortalities after 3 rd day. No mortalities were noticed in stocks which were used as positive control and negative control.…”
Section: Resultsmentioning
confidence: 99%
“…The severity of inhibition was determined by parallel streaking method 10 . The inhibitory activity of the producer (antagonistic) strain was determined on the basis of growth inhibition of the test strain and the severity of inhibition was rated as "++" for total inhibition, "+" for feeble / thin growth and "-" for no inhibition and comparison with control plates.…”
Section: Inhibitory Activity Of Antagonistic Bacteriummentioning
confidence: 99%